Phorbol esters from Jatropha meal triggered apoptosis, activated PKC-δ, Caspase-3 proteins and down-regulated the proto-oncogenes in MCF-7 and HeLa cancer cell lines - Oskoueian, Ehsan; Abdullah, Norhani; Ahmad, Syahida (MDPI, 2012)
Jatropha meal produced from the kernel of Jatropha curcas Linn. grown in Malaysia contains phorbol esters (PEs). The potential benefits of PEs present in the meal as anticancer agent are still not well understood. Hence, this study was conducted to evaluate the cytotoxic effects and mode of actions of PEs isolated from Jatropha meal against breast (MCF-7) and cervical (HeLa) cancer cell lines. Isolated PEs inhibited cells proliferation in a dose-dependent manner of both MCF-7 and HeLa cell lines with the IC50 of 128.6 ± 2.51 and 133.0 ± 1.96 µg PMA equivalents/mL respectively, while the values for the phorbol 12-myristate 13-acetate (PMA) as positive control were 114.7 ± 1.73 and 119.6 ± 3.73 µg/mL, respectively. Microscopic examination showed significant morphological changes that resemble apoptosis in both cell lines when treated with PEs and PMA at IC50 concentration after 24 h. Flow cytometry analysis and DNA fragmentation results confirmed the apoptosis induction of PEs and PMA in both cell lines. The PEs isolated from Jatropha meal activated the PKC-δ and down-regulated the proto-oncogenes (c-Myc, c-Fos and c-Jun). These changes probably led to the activation of Caspase-3 protein and apoptosis cell death occurred in MCF-7 and HeLa cell lines upon 24 h treatment with PEs and PMA. Phorbol esters of Jatropha meal were found to be promising as an alternative to replace the chemotherapeutic drugs for cancer therapy.